Turboset shaft voltage - Klasnić, Ilija G (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
The paper presents an analyses of shaft voltage and bearing current phenomena in electrical machines. An overview of the causes of these voltages and currents and their possible consequences is also given. The influence of the thyristor excitation system on the level of shaft voltages is examined, followed by the proposal of a measuring method and the preventive measures for shaft voltage reduction. Finally the paper reports the experimental measurements of shaft voltages on a turbo set that is a part of the Electric Power Industry of Serbia